Evolution of agriculture: the origin of our food crops - Schreiber, Mona (Henry Stewart Talks, 2021)
The evolution of agriculture, The Neolithic transition, The fertile crescent, The spread of the new lifestyle, Domestication, The domestication and diversity of barley, The evolution of weeds and rye as a secondary domesticate